The FAR model: assessing quality in interlingual subtitling - Jan Pedersen (JoSTrans: The Journal of Specialised Translation)
To this day, there exists only a generalized quality assessment model for intralingual (live) subtitles for the deaf and hard of hearing – the NER model. Translated subtitles seem to be quality assessed mainly using in-house guidelines. This paper contains an attempt at creating a generalized model for assessing quality in interlingual subtitling. The FAR model assesses subtitle quality in three areas: Functional equivalence (do the subtitles convey speaker meaning?); Acceptability (do the subtitles sound correct and natural in the target language?); and Readability (can the subtitles be read in a fluent and non-intrusive way?). The FAR model is based on error analysis and has a penalty score system that allows the assessor to pinpoint which area(s) need(s) improvement, which should make it useful for education and feedback. It is a tentative and generalised model that can be localised using norms from guidelines, commissioner specs, best practice etc. The model was developed using existing models, empirical data, best practice and recent eye-tracking studies and it was tried and tested on Swedish fansubs.